Development of a 1.0 KVA Fuelless Generator - Aliemeke, Blessing Ngozi Goodluck; Momoh, Munirat Abdullawal; Asekhome, Mercy Onoshioze; Anani, Christian Azuka; Vincent, Afoke Chief (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
A 1.0 KVA fuelless generator has been developed. The crave for sustainable energy solution has led to the exploration of emerging technologies targeted at reducing reliance on fossil fuels and reducing environmental impact. One such technology is the development of fuelless generators, which harness renewable energy sources or utilize unconventional mechanisms to generate electricity. This power producing mechanism is aimed to develop a targeted 1KVA power capacity through innovative design strategies. Detailed graphical modeling of the orthographic projection and isometric views brought about enhanced machine components development for stability and reliability. Careful selection of conductor materials and design considerations ensured efficient power transmission, minimizing losses within the system. Integration of power factor correction capacitors and advanced control algorithms contributed to achieving a power factor close to unity, optimizing energy utilization. Comprehensive performance testing validated the functionality and reliability of the developed generator under various load conditions. The development of a fuelless generator with a battery power capacity of 0.85 Kw, torque of 14.48 Nm, resistance of 48.35 ohms, current of 4.55 Amperes and a power factor of 0.85 signifies a significant breakthrough in sustainable energy generation. The performance test showed that that an input response brought about an increase in load (W). The success of developing the generator not only demonstrates the feasibility of clean and sustainable energy solutions but also underscores the potential for further advancements in fuelless generator technology towards a more reviving energy prospect.